Analysis of Kurma Nabeez in 1-7 Day Partum Party on Increasing ASI and Baby Body Production in BPM Ririn R. Sudimoro, Bululawang Districts Malang - Indriati, Ina (Master of Public Health Program Universitas STRADA Indonesia, 2020)
Nabeez water is marinated water from dates, now also known as infused water. Potassium or potassium contained in dates will block dopamine receptors, and then stimulate prolactin release. In the presence of high prolactin, breast milk production will increase. Prolactin is widely found in breastfeeding mothers, because prolactin is important for stimulating the mammary glands that are useful for producing milk. If the mother's nutrition is good, the milk produced will be of good quality and strength. This study aims to analyze Nabeez Dates on increasing breast milk production and increasing infant weight. The research design used is quantitative research using the experimental quasi approach post-test - only control design. The study was divided into two subjects, 15 respondents breastfeeding mothers given dates 5 items dates (around 45g) contain around 115 Kcal as a treatment group and 15 respondents nursing mothers as a control group for 7 days at BPM Ririn R Sudimoro Bululawang, Malang Regency. The results showed that breast milk production in the treatment group (15 respondents) on day 4 was still 60% in sufficient category, on days 5.6 and 7 it was 87% good than the control group. Increased infant weight in the treatment group (15 respondents) on days 4,5,6 and 7 in the treatment group most showed weight gain compared to the control group. The results of the statistical analysis using the Mann Whitney test obtained a significance value (p) of 0,000 <(α = 0,05), meaning that H0 was rejected and H1 was accepted, this means that there is an effect of nabeez dates on increasing milk production and increasing infant weight. Nabeez dates in postpartum mothers can increase milk production so that the needs of the baby will be fulfilled with breast milk both in quality and quantity